The impact of cybercrimes in the banking sector and the effects on the customer - Daka, Naledi Belita; Doucek, Petr, 1960-; Luc, Ladislav; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2023)
Cybercrime crimes affect people's lives, resulting in various effects, such as financial loss and leaking private information on the internet. The rapid growth of the internet and E-commerce and the many other transactions carried out in cyberspace has given rise to many cybercrimes. There has been an increase in cybercrimes on the African continent, and South Africa has one of the highest numbers of cybercrimes on the continent. The thesis aims to investigate cybersecurity awareness and the impact of bank-related cybercrime on clients and banks in South Africa. The methodology employs two approaches: primary data through an online questionnaire survey of 112 respondents and secondary data from the SABRIC reports. The findings identified that fraudsters' most common methods to commit these cybercrimes in digital banking are vishing, phishing, sim swap, smishing and personal or business email hacking. Cybercrime has led to significant impacts, including financial losses, the release of personal information, legal implications, and the erasure of personally identifying data. The effect of cybercrime on banking profits is linked to customer satisfaction, a decrease in customer satisfaction resulting in lower revenues. The linear regression trend of cybercrimes of the last five years (2017- 2021) and forecast till 2030 shows that losses in costs caused by cybercrime in the banking sector are anticipated to rise in the upcoming years. The awareness of clients on various bank-related cybercrimes showed partial understanding. The thesis recommends how education and training can raise awareness of banks and their clients can be protected from data breaches, personal data loss and financial losses incurred.
Vedoucí práce: Petr Doucek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: information systems management [obor dipl. práce]; diplomové práce; master's theses